(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2024)
Nowadays due to the advancement of technology students waste much of their study time in using social media rather than dealing with academic issues. As a result of this, the main objective of this study was to examine the effect of social media on reading and listening habits of polytechnic students, a case study of The Polytechnic, Ibadan. The descriptive research method was adopted for this study and five departments were sampled with the use of simple random sampling technique. A total number of 150 pupils were drawn from the total population of the sampled department. A total number of 150 copies of questionnaire were duly filled, retrieved and used for the study analysis. Descriptive statistics of simple percentage was adopted in the analysis of data of the study. Furthermore, the data output revealed that students spent an average of 6.10 hours and 7.24 hours per day in using different social media accounts than dealing with studying their academic subject matters.